2003
DOI: 10.1080/0264041031000102015
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of cycling in relation to anterior knee pain and patellar tendinitis

Abstract: The coronal and sagittal plane leg movements of 24 experienced male cyclists were assessed using video analysis while cycling on a Kingcycle windload simulator. The cyclists were grouped into those with a history of injury and an asymptomatic group on the basis of self-reported injury status. The ages, cycling experience, competition distances and competition speeds of the two groups were compared using Student's t-test. No significant differences (P < 0.05) were found for any of these variables. The maximum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
46
3
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 12 publications
6
46
3
2
Order By: Relevance
“…Em busca de soluções para algumas destas dúvidas, diversos protocolos de avaliação biomecânica da pedalada são utilizados (4,10,13). Com base na cinemetria, alguns modelos para análise do movimento em duas ou três dimensões têm sido desenvolvidos, com o propósito de explicar as característi-cas mecânicas do movimento cíclico realizado pelos membros inferiores durante a pedalada (1,8,12). Tais análises se tornam, ainda, mais completas quando se têm associados à cinemetria outros métodos de medição, como a dinamometria.…”
Section: Introductionunclassified
“…Em busca de soluções para algumas destas dúvidas, diversos protocolos de avaliação biomecânica da pedalada são utilizados (4,10,13). Com base na cinemetria, alguns modelos para análise do movimento em duas ou três dimensões têm sido desenvolvidos, com o propósito de explicar as característi-cas mecânicas do movimento cíclico realizado pelos membros inferiores durante a pedalada (1,8,12). Tais análises se tornam, ainda, mais completas quando se têm associados à cinemetria outros métodos de medição, como a dinamometria.…”
Section: Introductionunclassified
“…In particular, a kinematic analysis of the hip, knee, and ankle during leg cycling may help identify incorrect movement patterns, [21][22][23] which can be used to design an optimal rider-bike configurations, in order to promote safe and effective pedaling. Understanding the possible differences in leg movement patterns between AB and SCI individuals may provide insight into ways to redesign FES-LCE systems and thus enhance its potential clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…In their literature review on injuries and cyclists, Pruitt and Matheny (2006) emphasized that because pedaling is characterized by repetitive movements compared with other exercises, improper posture or loading can easily cause injuries. In their study, Bailey, Maillardet, and Messenger (2003) found no large difference in sagittal joint angle but found marked differences in knee joint angle in the frontal plane according to the presence or absence of a history of overuse injury. Therefore, as differences in pedaling technique and muscle revelation may be expected between elite and amateur cyclists, the need for examining the activation of pedaling-related joints and muscles is suggested in order to assess the efficiency of the pedaling performance.…”
mentioning
confidence: 99%